FOOD MARKETS IN POLAND AND LATVIA - THIERS CAPACITY AND COMPETITIVENESS - Rytko, Anna (Acta Scientiarum Polonorum. Oeconomia, 2016)
The objective was to identify the capacity of the food markets in Poland and Latvia, and their level of competitiveness. Market capacity decrease was observed in both countries, measured the decline in the shares of expenditure on food and the decrease of final food and non-alcoholic beverages consumption expenditure (in Poland, the level of consumption in 2013 was around 43 billion EUR and Latvia 2.7 billion EUR).The effects of declining demand for food were more than offset by the fast-growing export, which in 2014 in Poland and Latvia respectively amounted more than 20 billion EUR and more than 2 billion EUR. The value of export, in the years 2005-2014, in Latvia has increased more than four times, and in Poland and has tripled. Polish and Latvian foods, during the period, was competitive in foreign markets, although the observed high levels of competitiveness are lowered. In 2011, in Poland 11 product groups was characterised by a high or very high competitiveness, in Latvia much more - 23. Monitor levels of competitiveness is necessary, in particular, the rapidly growing competitiveness of import of some product groups, for example pig meat. Then the next step can be taken - looking for the reasons for these phenomena, as well as to take the appropriate action on the administrative and legal sphere.